Removal of nitrogen and organic matter in an intermittently aerated horizontal subsurface flow constructed wetland - Queluz, João G. T. [UNESP]; Garcia, Marcelo Loureiro [UNESP] (Journal of Urban and Environmental Engineering, 2020)
The objective of this work was to evaluate the effect of intermittent aeration on the removal of ammonium (NH4+), total nitrogen (TN) and chemical oxygen demand (COD) in a horizontal subsurface flow constructed wetland (HFCW). Two HFCWs were studied, one non-aerated and another aerated intermittently, and both cultivated with Typha latifolia. Each system received 8.6 L d-1 of synthetic wastewater, resulting in 3 days of hydraulic retention time. The two systems displayed high efficiencies in the removal of COD (>90%); however, the intermittently aerated HFCW showed a higher rate of COD removal. Additionally, the removal of TN (48.8%) and NH4 + (57.7%) in the non-aerated system was limited, while in the aerated system, the efficiencies of TN (81.2%) and NH4+ (98.6%) removal were satisfactory. Thus, the results indicate that via intermittent aeration, nitrification and denitrification occur simultaneously, improving the performance of HFCW in the removal of TN and NH4+.
Keywords: Artificial aeration; Constructed wetlands; Nutrients removal; Rural sanitation; Wastewater treatment